The "FIFA 11+" warm-up programme for preventing injuries in soccer players: a systematic review - Alex de Andrade Fernandes; Cristiano Diniz da Silva; Israel Teoldo da Costa; João Carlos Bouzas Marins
Introduction Soccer is among the sports with the highest injury rate. A group of international experts from the Fédération Internationale de Football Association - FIFA's Medical Assessment and Research Centre - have developed the "FIFA 11+", a warm-up programme whose main goal is to reduce the risk of common injuries in both male and female soccer players. Objective To conduct a literature review in order to check the efficiency of the "FIFA 11 +" warm-up programme in preventing injuries in soccer players. Methods We conducted a systematic review of studies in the databases MEDLINE/PubMed, SciELO, ScienceDirect and SPORTDiscus, using the following keywords in combination with one another: "injury", "prevention" and "warm-up". Results Five studies met the inclusion criteria. In four studies, the authors conclude that the "FIFA 11 +" warm-up programme is effective for preventing injuries in soccer players. In one study, this protective effect was not observed. Conclusion The analyzed studies indicate that the FIFA 11+ warm-up programme for the prevention of sports injuries show positive signs that the use of the programme may help reduce the incidence of injuries in girls aged 13-17 years. In a male children population the results are inconclusive and further research is needed.